The origin of driftwood on eastern and south-western Svalbard - Linderholm, Hans W.; Gunnarson, Björn E.; Fuentes, Mauricio; Büntgen, Ulf; Hormes, Anne (Polar Science, 2021)
The Arctic is one of the regions where the effect of global change is most evident. Associated with warming are changes in snow, sea ice and hydroclimate, all which have significant impacts on environments and society. However, due to short observational records, it is difficult to set the current climate in a long-term context. Arctic driftwood (DW), available throughout the Holocene, is a paleoclimate resource that may shed information on past sea-ice, ocean current and atmospheric conditions because it is transported by sea ice across the Arctic. Moreover, DW tree-ring data can be used to interpret climate in the boreal forests where the trees grew. Here we present a study of 380 DW samples collected on eastern and south-western Svalbard. Combining species identification and dendrochronology, it was found that the DW mainly consisted of Pinus sylvestris, Picea sp. and Larix sp. (87% of all samples), mainly originating from northern Russia. In total, 60% of the DW could be dated and their provenance determined, and four tree-ring width chronologies representing Yenisei and Dvina-Pechora were constructed, facilitating extension and improvement of the existing chronologies representing those regions. Moreover, DW from relict beaches that can be subjected to dendrochronological analyses, provides possibilities to extend pan-Arctic tree-ring data even further back in time. Because there are several processes governing the temporal patterns of wood deposition in the Arctic, using DW as an indicator of sea-ice variations needs further investigation